Flaps or flat: a case report of double free flap survival after a prolonged cardiac arrest - Atmodiwirjo, Parintosa; Ramadan, Mohamad Rachadian; Djohan, Michael; Amanda, Nadira Fildza (Faculty of Medicine Universitas Indonesia, 2024)
This case addressed patient and free flap survival after cardiac arrest with the contentious use of vasopressors amid concerns about potential vasoconstrictive effects on flap vitality. A 59-year-old male with mucoepidermoid carcinoma underwent post-total maxillectomy and double free flap reconstruction (free fibular flap and anterolateral thigh free flap). Intraoperatively, he experienced cardiac arrest after anastomosis due to hypovolemia or hypoxia, requiring external cardiac massage and vasopressor administration. Despite the initial restoration of circulation, subsequent cardiac arrest ensued, necessitating further resuscitation. Postoperatively, vasopressors were also administered due to hemodynamic instability. Contrary to concerns, both flaps demonstrated sustained vitality, challenging prevailing apprehensions about vasopressor-induced vasoconstriction compromising flap viability. This observation suggests that vasopressors may not significantly threaten flap viability, prompting reconsideration of hesitations and encouraging further investigation. The study advocates for a judicious evaluation of vasopressor administration in free flap procedures, enriching clinical considerations for optimal patient care.